TREatment of ATopic eczema (TREAT) Registry Taskforce: protocol for a European safety study of dupilumab and other systemic therapies in patients with atopic eczema. (20th November 2019) - Bosma, A.L.; Spuls, P.I.; Garcia‐Doval, I.; Naldi, L.; Prieto‐Merino, D.; Tesch, F.; Apfelbacher, C.J.; Arents, B.W.M.; Barbarot, S.; Baselga, E.; Deleuran, M.; Eichenfield, L.F.; et al.
Summary: Background: A long‐term prospective observational safety study is essential to characterize fully the safety profile of systemic immunomodulating therapies for patients with atopic eczema. The TREatment of ATopic eczema (TREAT) Registry Taskforce offers a large platform to conduct such research using national registries that collect the same data using a predefined core dataset. Objectives: To present a protocol for a safety study comparing dupilumab with other systemic immunomodulating therapies in children and adults with moderate‐to‐severe atopic eczema, to assess the long‐term safety risk of these therapies in a routine clinical care setting. Methods: We describe a registry‐embedded international observational prospective cohort study. Adult and paediatric patients who start treatment with dupilumab or another systemic immunomodulating agent for their atopic eczema will be included. The primary end point is the incidence of malignancies (excluding nonmelanoma skin cancer) compared between the treatment groups. Secondary end points include other serious adverse events and adverse events of special interest, such as eye disorders and eosinophilia. Conclusions: This protocol delineates a safety study for dupilumab in adult and paediatric patients with atopic eczema, using a standardized methodological approach across several national registries. The protocol could also be used for other novel systemic immunomodulating therapies, and could provide licensing and reimbursement authorities, pharmaceutical companies and clinicians with safety evidence from a routine clinical care setting. What's already known about this topic? There is a need for long‐term data on the safety of systemic immunomodulating therapies in patients with atopic eczema. Regulatory bodies, such as the European Medicines Agency, increasingly stipulate the collection of such data as part of the licensing agreement for new treatments, to assess the new agent's long‐term safety profile against established therapies. Large numbers of patients with a long duration of follow‐up are necessary in order to detect rare events like malignancies. What does this study add? The TREAT Registry Taskforce offers a platform to conduct such research with a network of multiple national atopic eczema research registries. We present a protocol for an investigator‐initiated multicentre safety study comparing dupilumab with other systemic immunomodulating therapies in adults and subsequently adolescents and children with moderate‐to‐severe atopic eczema. This protocol can be used as a framework for similar studies for other novel systemic immunomodulating therapies across both adult and paediatric populations. Abstract : Plain language summary available online